STRATEGI MENINGKATKAN MUTU PENDIDIKAN DI PERGURUAN TINGGI - Madinah, Sofyan (State Institute of Islamic Studies (IAIN) Palu, 2006)
Enhancing skill to manage and to develop university is urgently needed, including the adoption of modern managerial principles oriented to quality. To managers of university, quality management system is based on the ongoing improvement to strengthen and to improve. Monetary crises and free market have urged us to be more capable in deciding the future based on SWOT analyses. Kata Kunci : Strategi, mutu, pendidikan, perguruan tinggi